Tools for Embedding and Assessing Sustainable Development Goals in Engineering Education - Fermín Sánchez-Carracedo (MDPI AG, 2021)
This paper presents three tools developed within the framework of the project EDINSOST2-SDG, aimed at embedding and assessing the Education for Sustainable Development (ESD) in Engineering curricula. ESD is promoted through the introduction into engineering curricula of learning outcomes related to sustainability and, specifically, to the Sustainable Development Goals (SDG). The first tool, the “Engineering Sustainability Map”, contains ESD-related learning outcomes that any engineering student should have acquired upon completion of their studies. These learning outcomes are described according to four sustainability competencies: (1) Critical contextualization of knowledge, (2) Sustainable use of resources, (3) Participation in community processes, and (4) Application of ethical principles. The second tool, the “Sustainability Presence Map” of a degree, shows the percentage of the presence in the curriculum of each sustainability competency. The calculation of the presence of each competency is based on the effective integration of the related learning outcomes into a specific curriculum. Respective data are provided by teachers responsible for the coordination of the different subjects of the degree, collected by means of a questionnaire. The third tool presented is a questionnaire aimed at measuring the level of ESD that students perceive they have acquired through each competency. The comparison of data resulting from the Sustainability Presence Map with the data from the student questionnaire is the first step that allows the effectiveness of embedding ESD in a degree to be determined, a proper learning assessment will confirm such effectiveness. The three tools presented in this work have undergone a validation process and are currently being used in a set of engineering degrees related to the EDINSOST2-SDG project. The results of the application of these tools are part of the future research work of the authors.